2017
DOI: 10.1152/ajpcell.00119.2017
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two niches: differential functions for VCAM-1 in satellite cells under basal and injured conditions

Abstract: Cell-cell adhesion molecules play key roles in maintaining quiescence or promoting activation of various stem cells in their niche. Muscle stem cells called satellite cells (SC) are critical for skeletal muscle regeneration after injury, but little is known about the role of adhesion molecules in regulating the behavior of these stem cells. Vascular cell adhesion molecule-1 (VCAM-1) is a cell-cell adhesion protein expressed on quiescent and activated SC whose function is unknown in this context. We deleted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Our data on the composition of platelet releasate revealed that known key growth factors driving myoblast and/or chondrocyte proliferation such as PDGFBB and VEGFA were increased several fold in SR (Kieswetter, Schwartz, Alderete, Dean, & Boyan, ; Scully, Sfyri, et al, ). VCAM‐1 was previously shown to increase cardiomyocyte proliferation and skeletal myoblast differentiation and was 3.8‐fold more abundant in SR compared with physiological releasate (Choo, Canner, Vest, Thompson, & Pavlath, ; Iwamiya, Matsuura, Masuda, Shimizu, & Okano, ). Similarly, growth factors driving fibroblast proliferation such as EGF and FGF‐2 were increased 1.92‐ and 3.43‐fold, respectively (Yu, Matsuda, Takeda, Uchinuma, & Kuroyanagi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data on the composition of platelet releasate revealed that known key growth factors driving myoblast and/or chondrocyte proliferation such as PDGFBB and VEGFA were increased several fold in SR (Kieswetter, Schwartz, Alderete, Dean, & Boyan, ; Scully, Sfyri, et al, ). VCAM‐1 was previously shown to increase cardiomyocyte proliferation and skeletal myoblast differentiation and was 3.8‐fold more abundant in SR compared with physiological releasate (Choo, Canner, Vest, Thompson, & Pavlath, ; Iwamiya, Matsuura, Masuda, Shimizu, & Okano, ). Similarly, growth factors driving fibroblast proliferation such as EGF and FGF‐2 were increased 1.92‐ and 3.43‐fold, respectively (Yu, Matsuda, Takeda, Uchinuma, & Kuroyanagi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even if Integrin α7β1 is initially highly expressed in differentiated myotube, a switch in integrin signature is needed for proper myoblast proliferation and differentiation 24 . Itgα4 expression is induced in SC right after skeletal muscle injury to promote SCs’ activation and proliferation 25 , while Itgα5, has a crucial role in SCs’ migration and adhesion 26 .…”
Section: Discussionmentioning
confidence: 99%
“…CD106 is a trans-membrane protein in the immunoglobulin superfamily that has been successfully used for isolation of mouse MuSCs ( Liu et al, 2015 ). Importantly, expression of this protein in quiescent cells is required for maintenance of their basal function and prevention of premature lineage progression ( Choo et al, 2017 ). The current study demonstrates, for the first time, that CD106 is a reliable marker for the isolation of a highly enriched MuSC population from various rat skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%